Thermosensitive Bioadhesive Hydrogels Based on Poly(N-isopropylacrilamide) and Poly(methyl vinyl ether-alt-maleic anhydride) for the Controlled Release of Metronidazole in the Vaginal Environment - Ana V. Torres-Figueroa; Cinthia J. Pérez-Martínez; J. Carmelo Encinas; Silvia Burruel-Ibarra; María I. Silvas-García; Alejandro M. García Alegría; Teresa del Castillo-Castro (MDPI AG, 2021)
The development of thermosensitive bioadhesive hydrogels as multifunctional platforms for the controlled delivery of microbicides is a valuable contribution for the in situ treatment of vagina infections. In this work, novel semi-interpenetrating network (s-IPN) hydrogels were prepared by the entrapment of linear poly(methyl vinyl ether-alt-maleic anhydride) (PVME-MA) chains within crosslinked 3D structures of poly(N-isopropylacrylamide) (PNIPAAm). The multifunctional platforms were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, thermal techniques, rheological analysis, swelling kinetic measurements, and bioadhesion tests on porcine skin. The hydrogels exhibited an interconnected porous structure with defined boundaries. An elastic, solid-like behavior was predominant in all formulations. The swelling kinetics were strongly dependent on temperature (25 °C and 37 °C) and pH (7.4 and 4.5) conditions. The s-IPN with the highest content of PVME-MA displayed a significantly higher detachment force (0.413 ± 0.014 N) than the rest of the systems. The metronidazole loading in the s-IPN improved its bioadhesiveness. In vitro experiments showed a sustained release of the antibiotic molecules from the s-IPN up to 48 h (94%) in a medium simulating vaginal fluid, at 37 °C. The thermosensitive and bioadhesive PNIPAAm/PVME-MA systems showed a promising performance for the controlled release of metronidazole in the vaginal environment.